Regulatory T cells (Tregs) and their therapeutic potential against autoimmune disorders - Advances and challenges - Goswami, Tapas Kumar; Singh, Mithilesh; Dhawan, Manish; Mitra, Saikat; Emran, Talha Bin; Rabaan, Ali A.; Mutair, Abbas Al; Alawi, Zainab Al; Alhumaid, Saad; Dhama, Kuldeep (Human vaccines & immunotherapeutics, 2022)
Autoimmune diseases are caused when immune cells act against self-protein. This biological self-non-self-discrimination phenomenon is controlled by a distinct group of lymphocytes known as regulatory T cells (Tregs), which are key inflammatory response regulators and play a pivotal role in immune tolerance and homeostasis. Treg-mediated robust immunosuppression provides self-tolerance and protection against autoimmune diseases. However, once this system fails to operate or poorly operate, it leads to an extreme situation where immune system reacts against self-antigens and destroys host organs, thus causing autoimmune diseases. Tregs can target both innate and adaptive immunity via modulating multiple immune cells such as neutrophils, monocytes, antigen-presenting cells, B cells, and T cells. This review highlights the Treg-mediated immunosuppression, role of several markers and their interplay during Treg development and differentiation, and advances in therapeutic aspects of Treg cells to reduce severity of autoimmunity-related conditions along with emphasizing limitations and challenges of their usages.